THE EFFECT OF WORK DISCIPLINE AND WORK ENVIRONMENT ON THE PERFORMANCE OF EMPLOYEES (Sinergi : Jurnal Ilmiah Ilmu Manajemen, 2016)
Abstract.Of the many factors that influence employee performance, this research focuses on work discipline and working environment. Lack of discipline and inadequate working environment in the company, can have an impact on the implementation of the work process becomes inefficient. This study aims to determine the influence of labor discipline and the work environment to employee performance as well as the dominant variable influence on employee performance. The population in this study is an all employees at PT Ardian Putra MandiriSidoarjo totaling 126 people. The analysis model is a linear regression. Hypothesis testing using F test and t test at 5% significance level and supported by econometric tests. The results showed that jointly or in partial, work discipline and the work environment has a significant influence on employee performance. From both the independent variables studied, showed that having a dominant influence on employee performance is the work environment..